Kedudukan Hukum terhadap Pelaksanaan Tradisi“Wi’i Nggahi” sebagai Bentuk Perjanjian Pranikah pada Pernikahan Suku Donggo di Bima - Tria Nurfitriana; Ihlas; Zuhra (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the legal status of the Wi’i Nggahi tradition as a form of prenuptial agreement from a civil law perspective and to examine the legal consequences that arise if the agreement is not fulfilled by the time of marriage. This study employs an empirical legal research method with a sociological approach. Data were collected through interviews with traditional leaders and members of the Donggo tribe. The results of the study indicate that the Wi’i Nggahi tradition contains elements that meet the requirements for a valid agreement as stipulated in Article 1320 of the Civil Code, namely the existence of an agreement between the parties, legal capacity, a specific object and a lawful cause.